Reconstructing Teacher Competencies through Prophetic Pedagogy: A Systematic Analysis of Student Error Correction Based on Manhaj an-Nabawi fi Taqwim al-Akhta' - Ridho, Arman Maulana; Shobahiya, Mahasri; Ali, Mohammad (Universitas Muhammadiyah Surakarta, 2025)
This study aims to reconstruct teacher competencies through the lens of prophetic pedagogy by examining the Nabawi method of student error correction as articulated in Manhaj an-Nabawi fī Taqwīm al-Akhtā' by Muhammad Yusuf Al-Shatti. It seeks to address the theoretical gap in contemporary Islamic education literature by positioning error correction as a distinct analytical lens for understanding remedial teacher competencies.This research adopts a qualitative library research design employing interpretive text analysis and qualitative content analysis. The primary data source is Al-Shatti's work on Nabawi error correction, supported by contemporary scholarly literature on prophetic pedagogy, teacher competencies, and humane disciplinary approaches. Data were collected through close reading, thematic coding, and conceptual categorization, followed by thematic analysis to reconstruct communicative, psychological, spiritual, and strategic teacher competencies. Data credibility was ensured through source triangulation and thick description.The findings reveal that, within Nabawi pedagogy, student error is constructed as an inherent human phenomenon and a formative educational entry point rather than a disciplinary violation. Error correction is characterized by gradual instruction, empathy, dignity preservation, emotional safety, and moral justice. These principles give rise to integrative remedial teacher competencies that emphasize ethical communication, psychological regulation, restorative engagement, and spiritual orientation.This study offers an original contribution by reconstructing prophetic pedagogy as a coherent competency-based educational framework rather than a set of normative moral exemplars. It provides practical guidance for educators and policy makers seeking humane, dignified, and ethically grounded approaches to student discipline while enriching contemporary educational theory with a moral-spiritual perspective.